Methods for the assessment of human airway ciliary function. Issue 1 (28th July 2022) - Jackson, Claire L.; Bottier, Mathieu
Airway ciliary function analysis underpins PCD diagnostics and ex vivo / in vitro mucociliary clearance studies. It is an important measure of airway culture model integrity in health and after microbial/viral infections or airway drug therapies. https://bit.ly/3EXsG5J